2019
DOI: 10.1038/s41467-019-10838-1
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale perturbation of oxygen octahedra via surface ion exchange in perovskite nickelates boosts water oxidation

Abstract: A substantial amount of interest has been focused on AB O 3 -type perovskite oxides over the past decade as oxygen electrocatalysts. Despite many studies on various compositions, the correlation between the structure of the oxygen octahedra and electrocatalytic property has been overlooked, and there accordingly have been a very limited number of attempts regarding control of atomistic structure. Utilizing epitaxial Ln NiO 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 62 publications
4
90
0
Order By: Relevance
“…Moreover, it can also be observed that O K-edge sXAS spectra exhibit the increased intensity at OER conditions for all the catalysts (Fig. 3e), indicating the enhanced metal-oxygen covalency to promote the charge transfer between metal center and oxygen atoms during OER process 9,39 .…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, it can also be observed that O K-edge sXAS spectra exhibit the increased intensity at OER conditions for all the catalysts (Fig. 3e), indicating the enhanced metal-oxygen covalency to promote the charge transfer between metal center and oxygen atoms during OER process 9,39 .…”
Section: Resultsmentioning
confidence: 82%
“…For instance, Görlin et al reported that Fe 3+ species diminished the charge contribution process of Ni 4+ and stabilized Ni 2+ to improve the catalytic activity 35 . Oppositely, Fe 3+ species were also regarded as Lewis acid center to promote the formation of Ni 4+ species 36 , 37 , inducing the exacerbated geometric distortions and electronic structural variation 38 , 39 . Meanwhile, high valence Fe 4+ site was also detected by Mössbauer Spectroscopy to destabilize Ni 3+ species in the NiOOH lattice 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Epitaxial thin films have also been made by chemical rather than physical methods. The sol-gel method can be used to obtain thin films with different orientations [68,71] The ions for deposition are dissolved homogeneously mixed soluble salts in solutions that are applied onto the substrate by spincoating or similar techniques. The film forms upon chemical reaction of the solved ions with the substrate.…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…The symbol shape indicates the substrate and the color the B-site metal. The data was taken from refs [28,53,[62][63][64][65][66][67][68][69][70][54][55][56][57][58][59][60][61]…”
mentioning
confidence: 99%
“…The improved OER performance of perovskite oxide catalysts through oxygen vacancy creation via A site doping is also observed in similar systems, which show comparable performance to the PSFO catalysts documented in this study. 35,73,74,87,88 Figure 6 shows iR corrected CV scans where maximum current density response comes from the x = 0.5 sample. Table 3 displays the OER performance of similar rare earth single perovskite oxides in alkaline media, compared with the x = 0.5 material from this study.…”
Section: Electrochemistrymentioning
confidence: 99%